Design of a miniature fan for industrial applications - Liang, Zhengxi. (2012)
As electronic products become increasingly compact and powerful, one problem remains: high heat generation. This project was developed to look for a cooling solution that is able to generate airflow of 1.2 litres/sec and a pressure difference of 50 Pascal across a volume of 60mm by 60mm by 6mm, ultimately achieving the goal of faster heat dissipation. Incremental Design approach is employed to find the best solution to meet this project's objectives. The mechanics of an Injector and Dyson's Air Multiplier had a strong influence in this project's conceptual design. The design studied was to pass a motive fluid at 7 - 11m/s along an airfoil, NACA 2415's upper surface, to cause entrainment, resulting in an increase in flow at the outlet. CFD software, Ansys Fluent, was used to simulate the airflow across the CAD model. A 1:1 scale prototype and its test rig were fabricated for experimental data collection and airflow visualisation. Entrainment was observed to be approximately 250% of motive fluid, although not as high as the expectation of 1055%. Through the experiments conducted, the prototype was able to achieve approximately 0.483 litres/sec, 40% of the objective. Without an airfoil, flow separation is observed, resulting in backflow while an airfoil causes the flow to be directed uniformly from the inlet to the outlet.